2022
DOI: 10.1051/0004-6361/202244301
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fractionation towards a pre-stellar core traces isotope-selective photodissociation

Abstract: Context. Isotopologue abundance ratios are important to understand the evolution of astrophysical objects and ultimately the origins of a planetary system such as our own. With nitrogen being a fundamental ingredient of pre-biotic material, understanding its chemistry and inheritance is of fundamental importance to understand the formation of the building blocks of life. Aims. We aim to study the 14N/15N ratio in HCN, HNC, and CN across the prototypical pre-stellar core L1544. This study allows us to test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…We find that all three 14 N/ 15 N ratios increase when the external illumination grows in strength. HNC does present a slightly different response compared to CN and HCN in that its 14 N/ 15 N ratio increases less when G 0 is increased, but the overall trend is obviously different compared to what Spezzano et al (2022) observed in L1544. Also, even with the increased amount of external illumination, and hence a larger emphasis on the difference between self-shielding of N 2 and N 15 N, the simulation results still show only 1% level differences to the fiducial S3 simulation.…”
Section: Isotope-selective Self-shielding Of N 2 and Comentioning
confidence: 59%
See 3 more Smart Citations
“…We find that all three 14 N/ 15 N ratios increase when the external illumination grows in strength. HNC does present a slightly different response compared to CN and HCN in that its 14 N/ 15 N ratio increases less when G 0 is increased, but the overall trend is obviously different compared to what Spezzano et al (2022) observed in L1544. Also, even with the increased amount of external illumination, and hence a larger emphasis on the difference between self-shielding of N 2 and N 15 N, the simulation results still show only 1% level differences to the fiducial S3 simulation.…”
Section: Isotope-selective Self-shielding Of N 2 and Comentioning
confidence: 59%
“…Table 3 collects the parameters of the simulations, including details on the chemical network used in each simulation, and on the adopted physical parameters. In particular, in one simulation we test the effect of isotope-selective photodissociation for N 2 , considering that this has been invoked as an explanation for observed N fractionation gradients across the prestellar core L1544 (Spezzano et al 2022). The simulations S1, S2, and S3 represent, respectively, the center, inner region, and the outer envelope of a prototypical prestellar core.…”
Section: Simulation Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…3.). In dense interstellar clouds, dust grains rst accumulate refractory carbon and PAHs before acquiring ice mantles of simple species enriched in minor isotopes 36,37 . Noble gases are e ciently trapped in these mantles 38 and moderate chemical processing result in minor production of SOM 39 .…”
Section: Resultsmentioning
confidence: 99%